2018
DOI: 10.1002/jcp.27558
|View full text |Cite
|
Sign up to set email alerts
|

Ewing‐like sarcoma: An emerging family of round cell sarcomas

Abstract: Ewing‐like sarcomas are an emerging subgroup of small round blue cell sarcomas that share various degrees of morphological, immunohistochemical, molecular, and clinical similarity with Ewing sarcoma. Despite these similarities, Ewing‐like sarcomas lack the pathognomonic molecular hallmark of Ewing sarcoma: A translocation between a gene of the RNA‐binding TET family (EWSR1 or FUS) with a gene of the ETS‐transcription family ( FLI1, ERG, ETV1, ETV4, or FEV). Recently, increased use of modern molecular meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
55
0
5

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(61 citation statements)
references
References 65 publications
1
55
0
5
Order By: Relevance
“…ES is a kind of a class of diseases called small round cell malignant tumors. In such diseases, malignant tumor cells presented similar morphology, so it was hard to differentiate histology grade [20] [21]. In our study, we found that the most patients had missed grade data.…”
Section: Discussionmentioning
confidence: 66%
“…ES is a kind of a class of diseases called small round cell malignant tumors. In such diseases, malignant tumor cells presented similar morphology, so it was hard to differentiate histology grade [20] [21]. In our study, we found that the most patients had missed grade data.…”
Section: Discussionmentioning
confidence: 66%
“…CIC rearranged sarcomas are rare but represent the most frequent molecular subtype among Ewing-like undifferentiated SBRCTs [1,22], accounting for approximately 70% of SBRCTs lacking EWSR and FUS rearrangements [2,16,[23][24][25]. CIC rearranged tumors are characterized by fusions involving CIC, a human homolog of Drosophila Capicua located on chromosome 19q13.2 and encoding a transcriptional repressor, functioning downstream of tyrosine kinase receptor signaling.…”
Section: Discussionmentioning
confidence: 99%
“…Both DUX4 and DUX4L genes contain a 3.3-kb tandem repeat sequence located in the sub-telomeric regions of the long arms of chromosomes 4 and 10, respectively [28]. They encode for double-homeobox transcription factor typically expressed in germ cells as well as in the human testis, but epigenetically silenced by methylation in differentiated cells [1,[29][30][31]. No significant clinical-pathologic differences have been reported between tumors harboring the t(4;19) versus the t(10;19) [31].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The tumor suppressor gene EGR-1 can directly mediate the apoptotic function through the transcriptional upregulation of Bax-mRNA and protein and the increase of oligomerization and activation [32]. FEV is rich in alanine c-terminal, indicating that it may act as a transcriptional inhibitor [33]. FOS is considered as a regulator of cell proliferation, differentiation, and transformation and participates in MAPK signaling pathway [34,35].…”
Section: Discussionmentioning
confidence: 99%